Intravacuolar Pathogens Hijack Host Extracellular Vesicle Biogenesis to Secrete Virulence Factors - Gioseffi, Anna; Edelmann, Mariola J.; Kima, Peter E. (Frontiers in Immunology, 2021)
Extracellular vesicles (EVs) have garnered significant interest in recent years due to their contributions to cell-to-cell communication and disease processes. EVs are composed of a complex profile of bioactive molecules, which include lipids, nucleic acids, metabolites, and proteins. Although the biogenesis of EVs released by cells under various normal and abnormal conditions has been well-studied, there is incomplete knowledge about how infection influences EV biogenesis. EVs from infected cells contain specific molecules of both host and pathogen origin that may contribute to pathogenesis and the elicitation of the host immune response. Intracellular pathogens exhibit diverse lifestyles that undoubtedly dictate the mechanisms by which their molecules enter the cell’s exosome biogenesis schemes. We will discuss the current understanding of the mechanisms used during infection to traffic molecules from their vacuolar niche to host EVs by selected intravacuolar pathogens. We initially review general exosome biogenesis schemes and then discuss what is known about EV biogenesis in Mycobacterium, Plasmodium, Toxoplasma, and Leishmania infections, which are pathogens that reside within membrane delimited compartments in phagocytes at some time in their life cycle within mammalian hosts. The review includes discussion of the need for further studies into the biogenesis of EVs to better understand the contributions of these vesicles to host-pathogen interactions, and to uncover potential therapeutic targets to control these pathogens.